Building Character in The Midst of the Covid-19 - Imam Tabroni; Nur Aisah Jamil; Fitriani Nasihah; Rini Purnama Sari (East Asian Journal of Multidisciplinary Research, 2022)
Character deterioration that still occurs in many children or adolescents causes the need for efforts by various parties to provide character education to children from an early age. Parents as the first madrassa for their children have the most important role in educating the character of the child. This study aims to find out the ways or methods carried out by parents in educating the character of their children during covid-19. This study uses a mixed method by combining qualitative descriptive methods that describe events in the field which then researchers write the data into data in the form of numbers. The results showed that the way character education is carried out includes through a good example, giving advice orally, leaving the child to the teacher, limiting child association, giving explanations repeatedly, through habituation, being a good listener, giving praise, giving a mild threat or scaring the child. Based on this, it can be concluded that the role of parents in educating children's character is very important following their knowledge so that the results obtained can be maximal and following what is expected. This research is useful in making scientific and informational contributions on how to educate children's character